PENINGKATAN KOMPETENSI TATA BAHASA PRANCIS MAHASISWA JURUSAN PENDIDIKAN BAHASA PRANCIS FBS UNY DENGAN MODEL PEMBELAJARAN INQUIRY - Wilujeng, Nuning Catur Sri; Sumiyati, Siti; T. A., Anggraini Dora; Dwiyuliani, Titis (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2019)
(Title: Improving French Grammar Competence of The Students at French Departement, Faculty of Languages and The Arts, Yogyakarta State Uninersity Through The Inquiry Model). This research aimed to improve the students' French grammar competence through the Inquiry model with seven steps, ie : developing a question, generating a hypothesis, developing an experimental desain, collecting and recording data, analizing data, reaching conclusions, forming and extending generalizations, communicating results. This research was a class room action reseach study conducted in two cycles from the 2th to 27th May 2016. The research subjects were 21 students attending in Grammaire 4 in classes E and J at the French Departement, Faculty of Languages and the Arts, Yogyakarta State University. The data were collected through observations, field notes, and achievement test. They were analized using qualicative and quantitative descriptive techniques. The results of the study showed that the application of the inquiry model was capable of improving the students's French grammar learning, both in the process and the product. The success in the process was indicated by student's activeness in the learning activities for the Grammaire 4 through the inquiry model, and the average attainment in the first cycle was 70.47% and 77.1% in second cycle. The success in product was indicated by improvement of the students'French grammar competence, reflected by the improvement of average score of post-test. The difference between the average score of pre-test and post-test scores was significant because the result of the paired sample t-test both in the first cycle and second one was p (0.001) < 0.05. Keywords: inquiry model, French grammar, action research